Implementation of Read Aloud Feature from Microsoft Edge to Increase Pronunciation Ability Student’s - Farhan, Aldio Muhammad; Hadi, Muhamad Sofian (Jurnal Studi Guru dan Pembelajaran, 2024)
The aim of this research is to measure the effectiveness of learning media for students' pronunciation skills, which currently has a lot of misunderstanding regarding information about English pronunciation for students who are not native speakers of English. With this feature, it is certainly hoped that it will help in solving problems, and the Read Aloud feature from Microsoft Edge can be an alternative learning method. This research is specifically designed to improve students' abilities in English pronunciation, which makes the Read Aloud feature a learning medium. This research uses a qualitative method with a pre-experimental design. This research was conducted at SMPN 9 Tangerang Selatan involving 38 students from grade 7. The data used was taken from the pre-test and post-test. The data used is taken from the pre-test and post-test, based on the results taken from the t-test, Sig, 2 tail shows a result of 0.00, which is <0.05, therefore, there is a significant change from pre-test to post-test that affects student scores, therefore, the H0 hypothesis is rejected and H1 can be accepted. The results can be seen from the pre-test and post-test scores that show significant differences after being given treatment with the read feature aloud. The research results showed that the pre-test and post-test scores were (-19.21053) and the standard deviation was (6.52711). The mean standard error is 1,05884. The 95% confidence interval shows that the lower difference is (- 21.35593), while the upper difference is (-17.06512). The T-test result is (- 18.143) with df 37, and the two-sided test significance is 0.000 < 0.05.